Pengategorian Provinsi Berdasarkan Kelompok Sukses dan Gagal dalam Penanganan Pandemik Covid-19 di Indonesia Menurut Analisis Diskriminan - Endro Tri Susdarwono (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2021)
An assessment of categorizing the handling of Covid-19 by the Regional Government is needed, this categorization includes the handling performance (KP) and the death rate (TK) of Covid-19. This was done to see how serious the local government is in handling Covid-19. The approach in this study uses a descriptive approach, this approach aims to describe or describe the categorization of provinces based on groups that have succeeded and failed in handling the Covid-19 pandemic in Indonesia. In this research, the method used is quantitative method. The quantitative approach used is discriminant analysis. The conclusion of this study is that the discriminant function formed in this study is Z = 0.893 KP + 0.451 TK. The results of eigenvalues in this study indicate that the magnitude of Canonical Correlation is 0.797 or the amount of Square Canonical Correlation (CR2) = (0.797) 2 or equal to 0.635. So it can be concluded that 63.5% of the variation between groups of successful and failed provinces can be explained by the discriminant variables of the KP and TK ratios. The view of the matrix structure in this study shows that the amount of loading for KP is 0.842 and the amount of loading for TK is 0.332. The two variables of the Covid 19 handling ratio are high enough so that the discriminant score can be interpreted as a measure of the success of the handling of Covid 19 at the Provincial Government. Meanwhile, the results of the classification matrix show that 32 observations have been classified correctly and only two observations are classified incorrectly, namely the observations number 18 and 19, so the classification accuracy is (32/34) or 94.1%.